APLIKASI KEAMANAN DATA PROGRAM ACARA TV PADA TVRI MENGGUNAKAN METODE AES - Ismail Lubis; Fujiati Fujiati (CV. ADIBA AISHA AMIRA, 2023)
Confidentiality of data or information is very important information in an organization or a company which is a complete service. And in this technological age, it is an era where using a computer network where an irresponsible party can access a network access, this can result in the data transmission process being insecure because it is used by other parties who are not responsible for collect data or information that can be detrimental to certain parties. One way to maintain the security and confidentiality of data is to use cryptographic methods. In the field of cryptography, there are two very important concepts, namely encryption and description. The process of sending messages will go through an encryption process to convert the original text (plaintext) into ciphertext. So that it cannot be read or understood by other people and the confidentiality of the data and the integrity of the data to keep it safe